2021
DOI: 10.1039/d1cc05083d
|View full text |Cite
|
Sign up to set email alerts
|

Cation–π interactions enabling hard/soft Ti/Ag heterobimetallic cooperativity in lactide ring-opening polymerisation

Abstract: The combination of a Ti-salen complex with AgBArF reveals unique hard/soft heterobimetallic cooperativity in lactide ring-opening polymerisation (ROP), enabling significant activity at room temperature. Reactivity, mechanistic and computational studies highlight...

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(1 citation statement)
references
References 43 publications
(12 reference statements)
0
1
0
Order By: Relevance
“…In addition, the ONNO tetradentate structure in the salen-type ligand reduces the possibility of ligand exchange, which is beneficial for improving the stability of the catalyst. 19,[46][47][48][49][50][51][52][53][54][55] These features are important advantages for the development of a catalyst system that can be fine-tuned and potentially employed on an industrial scale. The pioneering studies in 1996 by Spassky reported that the (salen)Al complex with a large sterically hindered o-naphthalene bridged group could catalyze the ROP of LA to produce PLA with a high molar mass and narrow dispersity.…”
Section: Introductionmentioning
confidence: 99%
“…In addition, the ONNO tetradentate structure in the salen-type ligand reduces the possibility of ligand exchange, which is beneficial for improving the stability of the catalyst. 19,[46][47][48][49][50][51][52][53][54][55] These features are important advantages for the development of a catalyst system that can be fine-tuned and potentially employed on an industrial scale. The pioneering studies in 1996 by Spassky reported that the (salen)Al complex with a large sterically hindered o-naphthalene bridged group could catalyze the ROP of LA to produce PLA with a high molar mass and narrow dispersity.…”
Section: Introductionmentioning
confidence: 99%